Exosome: The “Off-the-Shelf” Cellular Nanocomponent as a Potential Pathogenic Agent, a Disease Biomarker, and Neurotherapeutics - Ghosh, Satyajit; Ghosh, Surajit (Frontiers in Pharmacology, 2022)
Exosomes are nanosized “off-the-shelf” lipid vesicles released by almost all cell types and play a significant role in cell–cell communication. Exosomes have already been proven to carry cell-specific cargos of proteins, lipids, miRNA, and noncoding RNA (ribonucleic acid). These vesicles can be selectively taken up by the neighboring cell and can regulate cellular functions. Herein, we have discussed three different roles of exosomes in neuroscience. First, we have discussed how exosomes play the role of a pathogenic agent as a part of cell–cell communication and transmit pathogens such as amyloid-beta (Aβ), further helping in the propagation of neurodegenerative and other neurological diseases. In the next section, the review talks about the role of exosomes in biomarker discovery in neurological disorders. Toward the end, we have reviewed how exosomes can be harnessed and engineered for therapeutic purposes in different brain diseases. This review is based on the current knowledge generated in this field and our comprehension of this domain.